2010
DOI: 10.1002/jbm.b.31631
|View full text |Cite|
|
Sign up to set email alerts
|

Functional apparent moduli as predictors of oral implant osseointegration dynamics

Abstract: At present, limited functional data exists regarding the application and use of biomechanical and imaging technologies for oral implant osseointegration assessment. The objective of this investigation was to determine the functional apparent moduli (FAMs) that could predict the dynamics of oral implant osseointegration. Using an in vivo dental implant osseous healing model, two FAMs, functional bone apparent modulus (FBAM) and composite tissue apparent modulus (FCAM), of the selected peri-implant structures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Concurrent with implant placement, M1 teeth on the contralateral side of the maxillae were extracted. In previous studies, ≈60% bone defect fill and 35% bone–implant contact were seen 14 days after implant placement 24,25 . To determine the gene expression profiles at early and late stages of healing, but prevent significant tissue damage while removing the implants, day 14 was selected as an endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…Concurrent with implant placement, M1 teeth on the contralateral side of the maxillae were extracted. In previous studies, ≈60% bone defect fill and 35% bone–implant contact were seen 14 days after implant placement 24,25 . To determine the gene expression profiles at early and late stages of healing, but prevent significant tissue damage while removing the implants, day 14 was selected as an endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…Because the removal process may damage the interfacial tissues, in a previous study the authors had demonstrated no radiographically detectable tissue deformation of cylindric mini-implants via FE analysis. 20 Therefore, the correlation coefficient from the functionally relevant peri-implant layer tended to be lower in the OA defects (Fig 5), and evaluation from the osseous defect area demonstrated significantly lower correlation to the original area after eliminating the artifact-affected area at day 10, especially for BV and FCAM (Table 1). One explanation is that the new bone or woven bone near the interfacial area does not provide strong fixation.…”
Section: Discussionmentioning
confidence: 95%
“…FAM, optimized from simulated loading on the dental implant, 20 could be more clinically relevant than any individual structural parameter, and the value of FAM would not change significantly with an increase in the cumulative peri-implant layer. Thus, the correlation coefficient between FAM and interfacial stiffness reveals the efficiency of the functionally relevant peri-implant layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations